Identification and Prioritizing Critical Success Factors for HR Shared Services Implementation in Multi-Business Firms Using DEMATEL Method - Fatemeh Goudarzi Hossainabadi; Mohammad Reza Akhavan Anvari; Kamyar Raissifar (International Journal of Management, Accounting and Economics)
Rapid developments in information technology and software have led organizations to adopt a new structure model known as shared services. A Shared Services Center (SSC) is an organizational concept companies use to allocate distributed resources efficiently. However, research has shown that some SSCs fail to achieve the expected efficiency improvements. Therefore, focusing on critical success factors for implementing a Human Resources Shared Services Center (HRSSC) can help organizations identify the factors necessary for success and avoid costly failures. The primary objective of this study is to identify and prioritize Critical Success Factors (CSFs) for implementing HRSSC in multi-business firms. The CSFs for implementing HRSSC have been identified. Furthermore, the interrelationships and influences among these factors have been examined using the DEMATEL paired comparison questionnaire. Among the identified factors, Leadership and Staff management, Organizational culture, Commitment of management, and a Clear and appropriate strategy have been ranked as the most important CSFs for implementing HRSSC in multi-business firms. Thus, managers and decision-makers should consider to these CSFs which are crucial to successful implementation of the Human Resources Shared Services Center in multi-business firms.